Immunologic monitoring during a phase 2a trial of the GNbAC1 antibody in patients with MS - Zimmermann, Maria (Neurol Neuroimmunol Neuroinflamm, 2015)
OBJECTIVE: To monitor the systemic immune responses of patients with multiple sclerosis (MS) under treatment with GNbAC1, a monoclonal antibody against the envelope protein of the MS- associated retrovirus, during a phase 2a trial. METHODS: We analyzed the composition of immune cell subsets and the activation level of monocytes by flow cytometry and the response against viral and vaccine antigens by ELISpot. RESULTS: None of the endpoints measured revealed any immunosuppressive effect of the therapeutic antibody. Activation of monocytes slightly decreased during treatment as predicted by the hypothesized mechanism of action of GNbAC1. CONCLUSION: These results support the conclusion that the antibody is safe for use in patients with MS. CLASSIFICATION OF EVIDENCE: This study provides Class III evidence that in patients with MS GNbAC1 does not significantly affect several biomarkers of systemic immune response.